2010
DOI: 10.1128/iai.00580-10
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli Disrupts Epithelial Cell Tight Junctions

Abstract: Enteroaggregative Escherichia coli (EAEC) is responsible for inflammatory diarrhea in diverse populations, but its mechanisms of pathogenesis have not been fully elucidated. We have used a previously characterized polarized intestinal T84 cell model to investigate the effects of infection with EAEC strain 042 on tight junction integrity. We find that infection with strain 042 induces a decrease in transepithelial electrical resistance (TER) compared to uninfected controls and to cells infected with commensal E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 44 publications
5
68
0
Order By: Relevance
“…Further work is required to better understand the relationship between these putative virulence markers and human clinical outcomes, though some tantalizing evidence suggests that Arcobacter has the potential to induce tight junction dysfunction (Bücker et al, 2009;Karadas et al, 2016), which may lead to diarrhea . This is similar to the effect observed with enteroaggregative E. coli (EAEC) infection (Strauman et al, 2010 (Wesley et al, 2000;van Driessche et al, 2005;Merga et al, 2011;Shah et al, 2013;Grove-White et al, 2014). Isolation rates vary between studies, but young cattle/calves were consistently shown to have higher Arcobacter carriage rates.…”
Section: Routes Of Transmissionsupporting
confidence: 64%
“…Further work is required to better understand the relationship between these putative virulence markers and human clinical outcomes, though some tantalizing evidence suggests that Arcobacter has the potential to induce tight junction dysfunction (Bücker et al, 2009;Karadas et al, 2016), which may lead to diarrhea . This is similar to the effect observed with enteroaggregative E. coli (EAEC) infection (Strauman et al, 2010 (Wesley et al, 2000;van Driessche et al, 2005;Merga et al, 2011;Shah et al, 2013;Grove-White et al, 2014). Isolation rates vary between studies, but young cattle/calves were consistently shown to have higher Arcobacter carriage rates.…”
Section: Routes Of Transmissionsupporting
confidence: 64%
“…T84 human colon intestinal epithelial cells, used as a model to study the effects of enterotoxins on TJ proteins (24,25,26,27,28,29), were obtained from the American Type Culture Collection. Cells (passage 5 to 18) were maintained in equal volumes of Dulbecco's modified eagle medium (DMEM) and F-12 supplemented with 5% (vol/vol) fetal bovine serum (FBS) (Invitrogen, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…STb24-31 was also tested at 4 nmol, and the effect on TJ proteins was similar to what is reported for 12 nmol (data not shown). The T84 cell line was used in our study because it was used for other E. coli enterotoxins (LT and STa) as well as V. cholerae and Yersinia enterocolitica enterotoxins although these act not in the colon but in the small intestine (24,25,26,27,28,29). This cell line exhibits tight junctions and desmosomes and maintains electrolyte vectorial transport; thus, T84 cells represent a reference for the work we had undertaken.…”
Section: Determination Of Assay Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar mechanism of action of P. aeruginosa was reported in bronchial epithelial cells where reduction in TER and disruption of ZO-1 were observed during infection [34]. Strauman et al, [35] showed that enteroaggregative Data represent mean ± SD from three independent experiments. *, statistical significance, using Student's t test, at P < 0.05; **, significance at P < 0.005.…”
Section: Discussionmentioning
confidence: 74%